An Efficacy of Covid – 19 Pandemic: Recovery of Workplace Environment and Ecosystem - Palanisamy Sivaprakash; Sivaprakash Kanchana; Ponnusamy Venkataramanan; Prawin Angel Michael (International Journal of Occupational Safety and Health, 2022)
The Covid-19 pandemic started in the late December 2019 and is still progressing globally at a rapid rate. The easy spreading nature of the covid-19 causative virus has made most of the countries to implement complete lockdown. The lockdown measure taken by most countries to combat the disease has not only assisted in decreasing the rate of spread but also the pollution of the workplace environment and environment as a whole. In the absence of most human and industrial activities that cause pollution, the nature is on its way in purifying itself. Without human intervention, the pollution free environment and its interaction with the ecosystem is bouncing back at a faster pace. The article explained the impact of lockdown measures on the reduction of environmental pollution on a global scenario.